PTU-159 Comparison of three commercially available point of care tests for coeliac disease. (22nd June 2015) - Mooney, PD; Wong, S; Burden, M; Kurien, M; Hadjivassiliou, M; Sanders, DS
Abstract : Introduction: Coeliac disease (CD) remains underdiagnosed. A rapid point of care test (POCT) may increase uptake of serological testing in appropriate patient groups. 3 POCTs are commercially available in the UK and in continental European pharmacy outlets: Biocard an IgA tissue tranglutaminase (tTG) test (BHR pharmaceuticals); Celiac Quick Test (Biohit Healthcare) detecting IgA, IgG and IgM tTG and Simtomax (Tillotts Pharma) which detects IgA and IgG antibodies against deamidated gliadin peptides (DGP). A fourth POCT has also been developed but not marketed (Xeliac Test Pro, Personal Diagnostics), with availability being solely from the manufacturer and no published data existing supporting its validity. Of the 3 commercially available POCTs, there is a limited evidence base with significant ascertainment bias. For this reason we decided to compare 3 commercially available tests in an endoscopic setting. Method: Patients referred with a positive endomysial antibody (EMA) for duodenal biopsy to confirm CD were recruited. All patients had repeat serum EMA, tTG and immunoglobulins and were tested simultaneously with the 3 POCTs as per the manufacturers' instructions. All patients had quadrantic duodenal biopsies from the second part of the duodenum as well as a duodenal bulb biopsy. Demonstration of villous atrophy (VA) was required to diagnose CD. Results: 82 patients (51.2% female, mean age 41.0) have been recruited. In 10 patients the EMA had normalised on repeat testing. None of these patients had VA on duodenal biopsy. 9 of these patients were referred with a weak EMA and had a negative tTG. One patient had a tTG of 10 times the upper limit of normal, and subsequent gluten challenge revealed a positive EMA and VA. Of the remaining 72 patients 59 new cases of CD were confirmed with the presence of villous atrophy, of the 13 EMA positive patients without VA 8 had Marsh 1 or 2 changes present with the remaining 5 patients having normal histology. Full sensitivity, specificity PPV and NPV for all of the tests compared to VA on duodenal biopsy are shown in Table 1. Conclusion: In this pilot data set Simtomax appears to be the most sensitive of the POCTs when compared to histology with similar results to serum tTG as screening test. Further work is required in larger cohorts and lower prevalence populations to confirm the utility of these tests in adult CD. Disclosure of interest: P. Mooney: None Declared, S. Wong: None Declared, M. Burden: None Declared, M. Kurien: None Declared, M. Hadjivassiliou: None Declared, D. Sanders Grant/ Research Support from: BHR pharmaceuticals; Tillotts Pharma for investigator led studies.